Janji Pemulihan Israel dalam Kitab Zefanya: Refleksi Teologi Kovenan - Daniel Pesah Purwonugroho; Sonny Eli Zaluchu (Jurnal Teologi Berita Hidup, 2019)
The God of the Israelites is a God of covenants that bind covenants with humanity. Agreement between them has a binding nature to one another. Throughout the history of the Israelites recorded in the Old Testament, God often spoke through His prophets. God delivered a special message about the lives of the Israelites and also what He promised them through these prophets. All messages in the Old Testament and the prophetic books refer to a conditional Covenant. On the one hand, God pursues and punishes, but on the other hand, He restores. The Covenant theology reveals God's intention to punish and repair that is manifested in Christ's mission. This paper analyzes the implementation of the covenant theology in the ministry of the Prophet Zephaniah through the study of literature and sees its implementation for the presence of Christ in the world.Abstrak: Allah adalah Allah perjanjian yang mengikat perjanjian kepada umat manusia. Perjanjian yang terjalin antara Allah dengan manusia memiliki sifat yang sangat mengikat. Di dalam kehidupan bangsa Israel yang terekam sepanjang kitab Perjanjian Lama, Allah bersabda melalui nabi nabiNya. Allah memberikan pesan secara spesifik perihal kehidupan bangsa Israel dan juga apa yang menjadi janjiNya kepada mereka. Seluruh pesan Perjanjian Lama dan khususnya kitab Nabi-nabi mengarah pada satu perjanjian atau kovenan bersyarat. Pada satu sisi, Allah menuntut dan menghukum tetapi pada sisi lain, Allah memulihkan. Teologi kovenan menampilkan maksud Allah untuk menghukum dan memulihkan yang tergambar di dalam misi Kristus. Tulisan ini menganalisis implementasi Teologi kovenan di dalam pelayanan Nabi Zefanya melalui studi literatur dan  melihat implementaisnya bagi kehadiran Kristus di dunia.